Protein malnutrition alters the distribution of Fc gamma R+ (T gamma) and Fc mu R+ (T mu) T lymphocytes in experimental pulmonary tuberculosis. - McMurray, D N (1990)
Inbred, strain 2 guinea pigs were given isocaloric diets containing either 30% (control diet) or 10% (low-protein diet) ovalbumin and infected 4 weeks later by the respiratory route with virulent Mycobacterium tuberculosis. By using an Fc receptor rosette assay, the proportions of T lymphocytes bearing Fc receptors for immunoglobulin G (T gamma cells) or immunoglobulin M (T mu cells) were quantified in blood and lymphoid tissues taken postinfection. A significant elevation in the proportion of the putative suppressor T subset (T gamma) in the blood of protein-deprived guinea pigs was observed at all intervals postinfection. Conversely, the levels of the putative helper T subset (T mu) in the bronchotracheal lymph nodes draining the site of virulent infection in malnourished animals were significantly reduced. Diet did not influence T gamma or T mu cells in the spleens. Diet-induced loss of purified protein derivative-specific T-cell functions in tuberculosis may be associated with alterations in the proportions of or the balances between T gamma and T mu subsets.